Isolated diastolic vs. systolic hypertension phenotypes and outcomes: prospective cohort of newly diagnosed individuals with hypertension. Issue 10 (October 2021) - Thomopoulos, Costas; Andrikou, Ioannis; Konstantinidis, Dimitris; Iliakis, Panagiotis; Kalos, Theodoros; Polyzos, Dimitrios; Drogkaris, Sotirios; Siafi, Eirini; Tousoulis, Dimitrios; Stergiou, George S.; Tsioufis, Costas
Abstract : Aims: To evaluate whether different hypertension phenotypes, namely, isolated systolic hypertension (ISH), isolated diastolic hypertension (IDH) and systolic/diastolic hypertension (SDH) have a differential outcome effect by clinic and ambulatory blood pressure (BP) measurements. Methods: We prospectively evaluated in 569 never-treated patients with sustained hypertension (age 52.6 ± 11.6 years; men 55%; clinic BP 150 ± 15/95.5 ± 10 mmHg, systolic/diastolic; 24-h ambulatory BP 128.9 ± 12.6/80.6 ± 9.7) the incidence of major cardiovascular (CV) events within 5 years, after adjustment for confounders, including the rate of BP control and the weighted follow-up BP. Results: All participants received antihypertensive drug treatment (mean number of drugs 1.9 ± 1.1; follow-up visits 4.6/patient). Average clinic BP achieved during follow-up was 136 ± 12.6/83.9 ± 9.4 mmHg, with 39% of participants having clinic BP less than 140/90 mmHg in at least 75% of their visits, and 24% in 25–75% of visits. Prevalence of hypertension phenotypes defined using BP differed from that using ambulatory BP, whereas integration of both BP measurements reclassified the initial phenotype to another in 18% of participants. Although, no differential outcome effect was observed between clinic IDH and SDH assessed using clinic or ambulatory BP measurements, clinic BP-based ISH was associated with a higher outcome incidence than the IDH and SDH phenotypes (hazard ratio 4.8, 95% confidence interval 1.4–17.0, P  = 0.015). ISH diagnosed by integration of clinic and ambulatory BP, also increased the outcome (hazard ratio 4.0, 95% confidence interval 1.0–15.6, P  = 0.046). Conclusion: In hypertensive patients at low/moderate CV risk, IDH and SDH phenotypes defined by clinic BP measurements, equally determined CV events but to a lower extent compared with ISH. Abstract : Supplemental Digital Content is available in the text